Endurance training adherence in elite junior netball athletes: A test of the theory of planned behaviour and a revised theory of planned behaviour - Palmer, C. L.; Burwitz, L.; Dyer, A. N.; Spray, C. M. (Journal of Sports Sciences, 2005)
This study examined the utility of Ajzen's (1985) theory of planned behaviour and Maddux's (1993) revised theory of planned behaviour to predict endurance training intentions and adherence of elite junior netball athletes. One hundred and fifteen athletes from the England Netball World Class Start Programme were assessed on constructs central to the predictions of the two theories. Adherence to a recommended endurance training programme was recorded in self-report diaries across a 9-week period. Validity for the diaries was supported by significant correlations (P ?<?0.001) with recalls across 7 days and 9 weeks. Adherence was moderate and variable between athletes (mean=66.05, s=25.75%). Two separate path analyses were conducted to examine the predictions of the theories. Goodness-of-fit indices suggested acceptable fit of the data to the models. Analyses showed that attitude towards the new behaviour, subjective norms and perceived behavioural control predicted training intentions. The relationship between intention and adherence was weak. The present results suggest that the constructs of the theory of planned behaviour offer some insight into the explanation of intentions to follow an endurance training programme. Constructs unique to the revised theory of planned behaviour did not significantly predict training intentions or behaviour. Implications for practitioners working with team sport performers are provided.